Strategi Pengembangan UMKM Industri Unggulan dengan Metode TOPSIS-SWOT - Yuvanda, Sesraria; Rasjid, Muhammad Rachmad; Nur, Deby Aisyah RJ (Universitas Batanghari Jambi, 2024)
Jambi City is a city that is experiencing growth and development in its industrial Micro, Small, and Medium Enterprises (MSMEs), with MSMEs contributing 37.68% to the overall industrial sector, out of a total of 6,416 industrial units in Jambi City. The objective of this research is to determine the leading industrial MSMEs and formulate appropriate strategies for fostering the development of these leading MSMEs. The research was conducted in Jambi City due to its highest number of MSME industrial units in the Jambi province. The determination of leading industrial MSMEs utilized the TOPSIS method, while the formulation of strategies for the development of leading industrial MSMEs employed a combination of TOPSIS-SWOT. The research findings indicate that the food sector is the leading industry for MSMEs in Jambi City. The recommended strategies for the development of the MSME industry include increasing product diversification through contemporary product designs, enhancing IT-based workforce competency, providing capital assistance and financial management support, and developing the online market..